Prospective teachers' perceptions of didactic obstacles in the online mathematics learning - Tatik Retno Murniasih; Vivi Suwanti; Syaharuddin Syaharuddin; Rahaju Rahaju; Nur Farida (Universitas Hamzanwadi, 2022)
The spread of the coronavirus has caused learning that was previously carried out offline to be online. It causes didactic obstacles in learning when implementing online learning. Research related to didactic obstacles has been widely studied from the perceptions of teachers and students but has not been widely studied from the point of view of prospective teachers. The purpose of this study is to investigate the didactic obstacles that arise in terms of the perceptions of prospective teachers in online mathematics learning. The method used in this research is descriptive qualitative. The research subjects were 18 prospective teachers divided into six groups, each consisting of three prospective teachers. The research locations were taken in two locations: East Java and Nusa Tenggara Timur (NTT). The instruments used include assignment sheets, field notes, field observations, and sheets for interviews with mathematics teachers in junior high schools. The triangulation technique compares the data from observations, interview recordings, and descriptions of answers. The research findings show that the biggest didactic obstacle occurs in the giving of too many assignments by the teacher to students. Giving too many assignments makes the quality of student work low. This result implies that teachers think giving students many assignments is natural so that all material is conveyed during the pandemic. It contradicts the perception of prospective teachers.